Multidimensional Integrated Stabilization Mission Efforts in Handling Humanitarian Conflict in Mali 2020-2023 - Susilowati, Ida; Sadiah, Nisa (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
In 2020-2023, humanitarian conflict in Mali increased du to the coup, which impacts on so that Mali's sovereignty. This research aims to analyze MINUSMA's efforts in dealing with humanitarian conflicts in Mali in 2020-2023. This research uses qualitative research with descriptive analysis method and international organization approach and Responsibility To Protect (R2P) liberalism perspective as the main approach. The data is taken from library research consisting of journals, books, news from official sources, documents, and international reports. The results of the research show MINUSMA's efforts in dealing with humanitarian conflicts in Mali through; infrastructure, security, health, politics and social. The concept of R2P consists of 3 pillars, namely; State responsibility, explains how the Malian government have failed to resolved the humanitarian conflict in Mali. MINUSMA as an international response updates the mandate of the resolution to ensure its effectiveness according to what happens on the ground. MINUSMA as a peace mission compresed by the United Nations served as a response to the international policy that has made several efforts to resolve humanitarian conflicts in Mali, among others: The MINUSMA providing patrol training to the military, implementing the PoC mandate and providing special protection to women and children. MINUSMA contributed to the long-term project of strengthening the airport, building QIPs projects, construction and rehabilitation in Mopti and government offices and public facilities in Segou. While a health policy by sending medical equipment, building laboratories and increasing understanding of health for the Malian people. MINUSMA organized conference activities and educational discussion for people with disabilities as well as restoring constitutional order and facilitating dialogue between transitional governments. This research describe efforts of MINUSMA as a UN peace mission to resolve humanitarian conflict in Mali.